Development of Somatic Embryogenesis and Plant Regeneration for Selected Malaysian Cocoa (Theobroma cacao L.) Clones from Zygotic Embryo Culture - Adrianti, Nahrud (2016)
Theobroma cacao L. which locally known as cocoa is a well-known member from the Sterculiaceae family. This species become commercially important commodity crop that can be profitable income for many developing countries. However, propagation of this valuable crop through conventional method is beset with many disadvantages. Consequently, the present study was carried out to develop an in vitro culture method for mass propagation of this species via somatic embryogenesis as a starting point for the production of plantlets and to compare which cocoa clones give the best response in somatic embryogenesis approach. The successful regeneration of somatic embryogenesis was obtained by using immature zygotic embryos as explants for the five selected local cocoa clones tested (PBC 230, BR 24, KKM 22, MCB C1 and MCB C2). For the induction of primary callus formation, DKW medium augmented with 0.5 mg/L 2,4-D and 1.0 mg/L 2,4-D with combinations of 25 μg/L TDZ produced the highest percentage of callus induction. Whereas, McCown’s salt with 2.0 mg/L 2,4-D and 50 μg/L 6-BA were found the optimum medium for the embryogenic callus induction. This study also highlighted the effectiveness of activated charcoal for the induction of somatic embryos. Among the embryo development mediums tested, DKW medium fortified with 1.0 mg/L activated charcoal was superior in the production of somatic embryogenesis with recorded the highest percentage explants producing somatic embryos. BR 25 showed the most responsive clone for the production of primary somatic embryogenesis compared to other four clones. During formation of secondary somatic embryogenesis, all clones showed better responses and multiplied rapidly. PBC 230 clones recorded the highest production of secondary somatic embryogenesis whilst MCB C2 exhibited low embryogenic potential in both primary and secondary production of somatic embryos. Besides, different survival rate during acclimatization and hardening also found among the clones tested. BR 25 showed better adaptation to the outside environment compared to the other clones. Meanwhile, all of MCB C2 plantlets failed to survive due to very low germination into normal plantlets, abnormalities and contaminations along the process. Five months observation after acclimatization process showed that somatic embryos-derived plants for all clones tested demonstrated normal growth phenotypes and similar morphology to the plants propagated by conventional methods. Fast and vigorous growing, quickly emission of new leaves and shoots, large leaf area and good branching habit characteristics indicated that the plants established normally as well as seedlings. Therefore, through this developed protocol, it is a great alternative for implementation of effective ways for mass propagation on more superior local cocoa clones and directly point out to enhance the development of cocoa planting industry in this country.